2004
DOI: 10.2298/hel0441151n
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific hybridization between H. pumilus Nutt. and H. annuus L. and their potential for cultivated sunflower improvement

Abstract: Successful interspecific hybridization was carried out between the wild perennial diploid species Helianthus pumilus Nutt., accession GT-M-172, and cultivated H.annuus L. The cross compatibility between H.pumilus and H.annuus was much higher when the wild species was used as the male in the crosses. Insemination (seed set) was very low in both directions. In order to prove the presence of considerable variability in the early F 1 generation, some statistical methods were used for evaluation of morphological tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…First, selfing rates were low ( fig. 4; table B8); thus, there is substantial self-incompatibility in H. pumilus, as noted by others (Nikolova et al 2004). This validates the experimental approach used to estimate fertility rates in the isolation plots by implying a low rate of seed set due to pollen flow from outside the plots.…”
Section: The Barrier Impedes Species-wide Adaptationsupporting
confidence: 65%
See 2 more Smart Citations
“…First, selfing rates were low ( fig. 4; table B8); thus, there is substantial self-incompatibility in H. pumilus, as noted by others (Nikolova et al 2004). This validates the experimental approach used to estimate fertility rates in the isolation plots by implying a low rate of seed set due to pollen flow from outside the plots.…”
Section: The Barrier Impedes Species-wide Adaptationsupporting
confidence: 65%
“…Improvement of the cultivated sunflower relies on introgression of valuable traits from wild, related species (Dorrell and Whelan 1978). Helianthus pumilis is of agricultural interest because of its pathogen resistance and its capacity to produce seeds with high linoleic fatty acid content under conditions that, in agricultural terms, would be considered extreme drought (Seiler 1994;Nikolova et al 2004). Barriers to hybridization with the cultivar are strong but incomplete, and fertile offspring, though not documented in the wild, have been produced under controlled conditions (Nikolova et al 2004).…”
Section: Study Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…argophyllus have high field tolerance to Phomopsis brown stem canker (Škorić, 1985). Nikolova et al (2004) observed field resistance to stem canker in progenies of interspecific hybrids of perennial Helianthus pumilus Nutt. Field resistance to Phomopsis was reported in interspecific hybrids derived from H .…”
Section: Biotic Traitsmentioning
confidence: 95%